2018
DOI: 10.3389/fnins.2018.00127
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E-Mimetic Peptide COG1410 Promotes Autophagy by Phosphorylating GSK-3β in Early Brain Injury Following Experimental Subarachnoid Hemorrhage

Abstract: COG1410, a mimetic peptide derived from the apolipoprotein E (apoE) receptor binding region, exerts positive effect on neurological deficits in early brain injury (EBI) after experimental subarachnoid hemorrhage (SAH). Currently the neuroprotective effect of COG1410 includes inhibiting BBB disruption, reducing neuronal apoptosis, and neuroinflammation. However, the effect and mechanism of COG1410 to subcellular organelles disorder have not been fully investigated. As the main pathway for recycling long-lived p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The therapeutic window for the treatment of acute brain injury animals expands to 2 h (Laskowitz et al, 2007), making it a potential protective agent for optic nerve injury treatment via intravenous administration. Several studies, including our previous research, assessed the neuroprotective effects of COG1410 on acute brain injury (Jiang and Brody, 2012; Li X. et al, 2018; Pang et al, 2018). COG1410 decreases JNK phosphorylation, iNOS protein levels and Bax expression, suggesting that COG1410 suppresses apoptosis possibly via inhibiting the p-JNK relative pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic window for the treatment of acute brain injury animals expands to 2 h (Laskowitz et al, 2007), making it a potential protective agent for optic nerve injury treatment via intravenous administration. Several studies, including our previous research, assessed the neuroprotective effects of COG1410 on acute brain injury (Jiang and Brody, 2012; Li X. et al, 2018; Pang et al, 2018). COG1410 decreases JNK phosphorylation, iNOS protein levels and Bax expression, suggesting that COG1410 suppresses apoptosis possibly via inhibiting the p-JNK relative pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, experiments have shown that both apoptosis and autophagy are activated in response to metabolic stress (Shliapina et al., 2021) or exposure to reactive oxygen species (Poillet‐Perez et al., 2015). Besides, autophagy pathway in brain is activated after the experimental subarachnoid hemorhage (SAH), which plays an important role in its EBI (Li X. et al., 2018). Autophagy precedes apoptosis, which has a protective effect in the early stages of programmed cell death (Jellinger & Stadelmann, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, autophagy pathway in brain is activated after the experimental subarachnoid hemorhage (SAH), which plays an important role in its EBI (Li X. et al, 2018). Autophagy precedes apoptosis, which has a protective effect in the early stages of programmed cell death (Jellinger & Stadelmann, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Vitek et al examined the effects of this APOE mimetic in a mouse model of AD, and found that the peptide ameliorates behavioral deficits and reduces plaques and tangles [193]. COG1410 was recently shown to upregulate autophagy via phosphorylation of GSK3β [194]. Given the fact that GSK3β regulates tau phosphorylation, this finding may present one of the mechanisms underlying the effects of COG1410 on the tangle pathology.…”
Section: Apoe Mimetic Peptidesmentioning
confidence: 99%